The elimination of child labour : whose responsibility? : a practical workbook - Bhargava, Pramila H., 1966- (New Delhi ; London : Sage Publications, 2003)
"This book reports a successful programme to tackle the social evil of child labour which was implemented by the author in a rural area of Andhra Pradesh. Without going into the pros and cons of child labour, the book is premised on the belief that it should be eliminated and emphasises that the only way this can be achieved is through education."--BOOK JACKET.
Foreword / C. Rangarajan -- 1. Child Labour: An Insight -- 2. Poverty and Survival: Occupations in which Children Are Engaged -- 3. Liberation through Freedom and Education -- 4. Towards a Better Life: Some Solutions -- 5. The Need for a New Vision: Bringing in Politicians, Bureaucrats and NGOs -- 6. Conclusion and Practical Solutions -- 7. Guide for New Endeavours: A Practical Workbook.
Includes bibliographical references.
Keywords: Child labor -- India